Hubungan Riwayat Pernikahan Dini dengan Status Gizi pada Balita di Kelurahan Keraton Wilayah Kerja Puskesmas Martapura 2 Tahun 2019 - Syifa, Siti Rahmatus; Rizani, Ahmad; Hapisah, Hapisah (JURNAL KEBIDANAN BESTARI, 2021)
Abstract Early marriage or marriage conducted under 20 years, has on impact bad for health moms and toddlers on of the effects results in the child born. This study aims to determine the relationship between the history of early marriage with nutritional status in infants in the kelurahan keraton working area of martapura 2 health center in 2019. The method of this study used a cross sectional approach using the chi-square test uji test with α = 0,05 and 95% confidence level. Population in this study 1240 children under five in the working area of martapura 2 health center. The sample in this study used the technique of accidental sampling with 10% of students in a total of 102 toddlers. The result of the study showed a history of early marriage of 65 people (64%). Normal nutritional status in toddlers was 72 toddlers (70,6%). The result of the chi-square test showed that there was a significant relationship with early history marriage with nutritional status of the children of ρ = 0.015 < α = 0.05 and OR 4,0. Repondents who early marriage has a normal chance compared to respondents who do not make early marriage 4 time the toddler has nutritional status is not normal. Statistical conclusions there is a relationship between the history of early marriage of status gizi toddlers in in the kelurahan keraton working area of martapura 2 health center in 2019 Keyword: Early Marriage, Nutritional status of toddlers